Using photovoice to identify sexual health needs in Latina early adolescents. Issue 1 (2nd January 2021) - Sanchez, Delida; Serrata, Josephine V.; Adams, Whitney; Arango, Sarah; Hamilton, Emma
ABSTRACT: Adolescence is a period of exploration of sexuality and of its integration into personality. Existing research on Latina adolescents, however, has been largely limited to disease and pregnancy prevention, ignoring the integration of sexual well-being with other aspects of health. Accordingly, this paper presents findings from a photovoice project with 11–12 year old Latina students, implemented to investigate topics related to cultural identity, gender and sexual health. The data were generated over a 12-week period in an urban middle school in Central Texas by 17 youth collaborators. Findings provide a platform for discussion of how Latina young people's ideas align with or diverge from current sexual health discourses within a racial/ethnic context. We highlight opportunities and constraints with regard to identifying sexual health needs from young Latina students' own perspectives, in an attempt to contribute to the body of literature on sexual health in middle school students, as well as the lessons learned through our efforts.